Myocardial Blood Flow and the Retinal Microvasculature Across the Spectrum From Normal to Failing Hearts - Jia Liu; Chang Chen; Zhongping Yu; Xuwei Chen; Zihao Chen; Wei Li; Min Ye; Xin He; Jiangui He; Juping Liu; Yugang Dong; Jan A. Staessen; et al. (The Journal of Clinical Hypertension)
ABSTRACT Deficiency of the myocardial microcirculation plays a role in the pathogenesis of heart failure (HF). We aimed to investigate the association of myocardial blood flow (MBF) and the retinal microvasculature with left ventricular (LV) function and its potential mediators. In healthy controls (HCs; n = 48), patients with cardiovascular risk factors (CVRF; n = 49) and patients with compensated HF (CHF; n = 52), we assessed LV diastolic filling pressure (E/e′), LV ejection fraction (LVEF), and global longitudinal strain (GLS) associated with MBF and the retinal arteriole‐to‐venule ratio (AVR), using multivariable regression models, while considering their direct contributions to LV function and the indirect contributions running via NT‐proBNP. Compared with HC, CHF had lower MBF and smaller AVR (p ≤ 0.002). In all participants, smaller AVR was associated with higher E/e′, lower LVEF, and lower GLS (p ≤ 0.010). Per 1 dB × dB/s MBF reduction, E/e′ increased by 0.09, whereas LVEF and GLS decreased by 0.46% and 0.14%, respectively (p < 0.001). The indirect contributions running via NT‐proBNP were all significant (p < 0.001) for MBF and for AVR related to GLS (p = 0.044) with mediation proportions of ≥29%. Across subgroups, these associations were directionally similar but lost significance given the lower sample size. Furthermore, across the spectrum of LV function, estimates of the associations of MBF with E/e′ and AVR with GLS showed a decreasing versus increasing trend (p ≤ 0.034). MBF and retinal microvasculature were associated with LV function and counterbalance the impaired LV function in CHF. NT‐proBNP, the natural vasodilating and natriuretic hormone, contributes close to 30% of the maintenance of LV function.